Checkpoint inhibition in meningiomas. (June 2016) - Bi, Wenya Linda; Wu, Winona W; Santagata, Sandro; Reardon, David A; Dunn, Ian F
Meningiomas are increasingly appreciated to share similar features with other intra-axial central nervous system neoplasms as well as systemic cancers. Immune checkpoint inhibition has emerged as a promising therapy in a number of cancers, with durable responses of years in a subset of patients. Several lines of evidence support a role for immune-based therapeutic strategies in the management of meningiomas, especially high-grade subtypes. Meningiomas frequently originate juxtaposed to venous sinuses, where an anatomic conduit for lymphatic drainage resides. Multiple populations of immune cells have been observed in meningiomas. PD-1/PD-L1 mediated immunosuppression has been implicated in high-grade meningiomas, with association between PD-L1 expression with negative prognostic outcome. These data point to the promise of future combinatorial therapeutic strategies in meningioma.